International Conflict between Law and Expediency - D. M. Fel’dman (Vestnik MGIMO-Universiteta)
The author examines the inconsistency between regulations currently in force and international law principles on the one hand and requirements of expediency and effectiveness of behavior of participants of international conflicts – on the other. The author reveals interconnections between the stability of individual international systems’ and global state-centric world system and conflicts and scenarios of interactions among actors of international conflicts.